2018
DOI: 10.1371/journal.pone.0192953
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of cover crops and no-till shift soil microbial community life strategies in agricultural soil

Abstract: Reducing tillage and growing cover crops, widely recommended practices for boosting soil health, have major impacts on soil communities. Surprisingly little is known about their impacts on soil microbial functional diversity, and especially so in irrigated Mediterranean ecosystems. In long-term experimental plots at the West Side Research and Extension Center in California’s Central Valley, we characterized soil microbial communities in the presence or absence of physical disturbance due to tillage, in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
99
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 76 publications
12
99
1
1
Order By: Relevance
“…However, meta-analyses of microbial communities to infer CSR strategies can be challenging due to the different factors related to experimental design and techniques employed across different studies, which could heavily affect the observations in comparison. Recent studies on soil-bacterial communities in cadmium-contaminated rhizospheres (Wood et al, 2018) and tillage-disturbed fields (Schmidt et al, 2018) also suggested the applicability of the CSR approach to soilmicrobial communities. To the best of our knowledge, the CSR framework has not yet been employed within a single study to changes in microbial communities upon disturbance in any microbiome other than soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analyses of microbial communities to infer CSR strategies can be challenging due to the different factors related to experimental design and techniques employed across different studies, which could heavily affect the observations in comparison. Recent studies on soil-bacterial communities in cadmium-contaminated rhizospheres (Wood et al, 2018) and tillage-disturbed fields (Schmidt et al, 2018) also suggested the applicability of the CSR approach to soilmicrobial communities. To the best of our knowledge, the CSR framework has not yet been employed within a single study to changes in microbial communities upon disturbance in any microbiome other than soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analyses of microbial communities to infer CSR strategies can be challenging due to 83 the different factors related to experimental design and techniques employed across different studies, 84 which could heavily affect the observations in comparison. Recent studies on soil-bacterial 85 communities in cadmium-contaminated rhizospheres (Wood et al 2018) and tillage-disturbed fields 86 (Schmidt et al 2018) also suggested the applicability of the CSR approach to soil-microbial 87 communities. To our knowledge, the CSR framework has not yet been employed within a single study 88 to changes in microbial communities upon disturbance in any microbiome other than soil.…”
Section: Introduction 44mentioning
confidence: 99%
“…Indeed, soil bacterial and fungal communities are known to change in association with plant traits that reflect plant productivity, such as foliar C:N and leaf dry matter content (Sayer et al, 2017). Links between plant CSR strategies, root exudates and the rhizosphere microbiome are also suggested by models (Krause et al, 2014;Schmidt, Gravuer, Bossange, Mitchell, & Scow, 2018;Thijs, Sillen, Rineau, Weyens, & Vangronsveld, 2018). Thus, changes in plant strategies along the productivity/disturbance gradients underpinning the humped-back curve should impose effects on rhizosphere biological diversity.…”
Section: Introductionmentioning
confidence: 99%